CRISIS OF EDUCATION OF STATE CIVIL SERVANTS AND RECONSTRUCTION OF A MODEL OF STRENGTHENING BUREAUCRATIC CAPACITY IN JAYAPURA REGENCY - Alienra Nanda Kadun; Yusuf Gabriel Maniagasi; Ibrahim Kristofol Kendi (International Journal of Multidisciplinary Reseach, 2026)
The quality of state civil servant (ASN) resources is a fundamental factor in realizing effective, accountable, and public service-oriented governance. However, empirical conditions in Jayapura Regency show that there is an inequality in the level of ASN education, especially the dominance of high school and S1 graduates and the limitations of ASN with S2 and S3 education. This condition has an impact on the weak analytical, managerial, and strategic capacity of the regional bureaucracy. This study aims to analyze the ASN education crisis and reconstruct the model of strengthening bureaucratic capacity based on formal education levels. The research uses a mixed methods approach by combining secondary data analysis from the Central Statistics Agency and the State Civil Service Agency, in-depth interviews with structural officials, and a study of personnel policy documentation. The results of the study show that the low proportion of civil servants with postgraduate education causes limitations in policy formulation, development planning, and public service innovation. In addition, the career development system and competency improvement of civil servants has not been fully based on organizational needs and meritocratic principles. Based on these findings, this study formulated a model for strengthening bureaucratic capacity that emphasizes the development of tiered education, improving performance-based competencies, strengthening the merit system, and strategic collaboration between local governments and universities. This model is expected to be able to improve the quality of government management and strengthen the competitiveness of regional bureaucracies in a sustainable manner. Theoretically, this research enriches the study of public administration and apparatus resource management, while practically providing policy recommendations for local governments in encouraging adaptive and competency-based bureaucratic reform.